AN ANALYSIS OF THE COMMON PURPOSE DOCTRINE AND RAPE IN SOUTH AFRICA WITH SPECIAL FOCUS ON TSHABALALA v THE STATE (2019) ZACC 48 - Khan, Franaaz; Hagglund, Kirstin (Obiter, 2022)
Violence against women, in particular, the crime of rape has reached epidemic status in South Africa. Rape constitutes a gross violation of the victim’s dignity, privacy, and person. It also intrudes upon the commitment between another man and the woman who is the victim to keep the intimacies of their bodily affections exclusively for one another. Rape is not only an act of contempt for the woman who is its victim but is also an act of contempt for the man or woman that she will choose or has chosen to commit herself. Rape is an act of violence, not only upon the woman who is its immediate victim, but towards the concept of family. The family is the granite cornerstone of society. Rape, by its definition, is the intentional, unlawful act of sexual penetration with a victim without their consent. The conundrum arises where a victim is confronted by a group of perpetrators but is only raped by one of them. Can the crime of rape be imputed to the other perpetrators who only watched and did not participate? The common purpose doctrine, a form of liability under South African common law, has been one of the few available measures which effectively addresses joint criminal ventures carried out by gangs. However, whether a conviction on a charge of rape on the doctrine of common purpose is legally competent has been the centre of legal debate. The main argument levelled against the imposition of liability for rape based on common purpose is that rape can only be committed through the instrumentality of an accused’s own body or part thereof, and not through the instrumentality of another. This paper seeks to discuss the effect of including the crime of rape in the doctrine of common purpose. The authors firstly discuss the doctrine of common purpose and rape. Thereafter, a discussion of the current legislative framework in South Africa follows as well as an analysis of the German criminal legal system. Finally, this paper seeks to advance and endorse the judgment handed down by the Constitutional Court in the case of Tshabalala v The State.